A study on Isolation and Characterization of Xylanase producing bacteria (Brevibacterium Brevis) - CHALLARAJ EMMANUEL E.S.,; APOORVA UDAYASHANKAR, (International Journal of Pharma and Bio Sciences, 2018)
Environmental impact of pollutants from paper and pulp industry was the strong driving force behind the endeavors leading to novel bleaching techniques. Xylanases are of great importance to pulp and paper industries as the hydrolysis of xylan facilitates release of lignin from paper pulp reduce the level of usage of chlorine as the bleaching agent. Xylanases that are produced by bacteria, fungi and actinomycetes improve the cleaning ability of detergents. Xylanases are extracellular enzymes which hydrolyze β-1, 4 D-xylosidic linkages of highly polymerized and substituted β-1, 4 linked D-xylobiose, xylotriose and glucucoronosyl residues, and are active between pH 4.5-7.5, at 30-60°C. In the present study a soil borne xylanase producing Brevibacterium brevis was isolated from soil samples. The isolate was biochemically identified and confirmed by 16SrRNA sequencing. The partial sequence was submitted in GenBank and was assigned with the accession number EU693514.The isolate showed good xylanase activity in the presence of rice bran and was clearly indicating less cellulose and 1,4-β-xylosidase activity. The xylanase which was confirmed on SDS –PAGE showing around 55- 66 KDa found productive at pH 9 at 35°C.